PREVENTION OF INFERIORITY COMPLEX ATTITUDES ACCORDING TO THE QUR'AN - Asnawiyah, A; Wahid, Abd; Amri, Nurullah; Husni, Muhammad Hadi (Universitas Muhammadiyah Surakarta, 2024)
Man as a caliph on earth was created by Allah in perfect form, but man is never free from emotional challenges such as the inferiority complex, which can hinder his spiritual and social development. The Qur'an calls for people not to feel this way, but also prohibits them from hitting the threshold that makes them arrogant, analysis is needed to find out the answer to how the mufassir interprets the verses related to the inferiority complex? And what are the limits of behaving so as not to have an inferiority complex attitude and not to result in arrogance? This study focuses on the analysis of mufassir's interpretation of Qur'anic verses related to the theme of inferiority complex, with the aim of understanding the boundaries of attitudes between arrogance and inferiority. This research is a literature review with a qualitative approach. The results of this study show that the mufassir emphasize that true strength lies in faith, solid faith is the initial key in overcoming the sense of inferiority complex, inferiority complex is the spiritual part of human beings and spiritual studies sourced from the Qur'an are the initial stages in fighting the inferiority complex. Allah commands His servants not to feel weak because they are created in the best form by Allah, with physical, intellectual, and spiritual virtues. Imam Qurthubi highlighted the importance of arousing enthusiasm and appreciating the privileges given by Allah without triggering behavior of superiority.